An antennal carboxylesterase from Drosophila melanogaster, esterase 6, is a candidate odorant-degrading enzyme toward food odorants - Chertemps, Thomas; Younus, Faisal; Steiner, Claudia; Durand, Nicolas; Coppin, Chris W.; Pandey, Gunjan; Oakeshott, John G.; Maïbèche, Martine (Frontiers in Physiology, 2015)
Reception of odorant molecules within insect olfactory organs involves several sequential steps, including their transport through the sensillar lymph, interaction with the respective sensory receptors, and subsequent inactivation. Odorant-Degrading Enzymes (ODEs) putatively play a role in signal dynamics by rapid degradation of odorants in the vicinity of the receptors, but this hypothesis is mainly supported by in vitro results. We have recently shown that an extracellular carboxylesterase, esterase-6 (EST-6), is involved in the physiological and behavioural dynamics of the response of Drosophila melanogaster to its volatile pheromone ester, cis-vaccenyl acetate. However, as the expression pattern of the Est-6 gene in the antennae is not restricted to the pheromone responding sensilla, we tested here if EST-6 could play a broader function in the antennae. We found that recombinant EST-6 is able to efficiently hydrolyse several volatile esters that would be emitted by its natural food in vitro. Electrophysiological comparisons of mutant Est-6 null flies and a control strain (on the same genetic background) showed that the dynamics of the antennal response to these compounds is influenced by EST-6, with the antennae of the null mutants showing prolonged activity in response to them. Antennal responses to the strongest odorant, pentyl acetate, were then studied in more detail, showing that the repolarization dynamics were modified even at low doses but without modification of the detection threshold. Behavioural choice experiments with pentyl acetate also showed differences between genotypes; attraction to this compound was observed at a lower dose among the null than control flies. As EST-6 is able to degrade various bioactive odorants emitted by food and plays a role in the response to these compounds, we hypothesize a role as an ODE for this enzyme toward food volatiles.